Proton pump inhibitor therapy and its association with spontaneous bacterial peritonitis incidence and mortality: A meta-analysis. Issue 4 (April 2016) - Yu, Ting; Tang, Yurong; Jiang, Liuqin; Zheng, Yongping; Xiong, Wenjie; Lin, Lin
Abstract: Background: Previous meta-analyses reported proton pump inhibitor (PPI) therapy is associated with increased incidence of spontaneous bacterial peritonitis (SBP) in cirrhotic patients. However, this conclusion was based on case–control studies. Moreover, the association between PPI use and mortality of SBP has not yet been confirmed. Aims: To evaluate the association between PPI use and SBP incidence and mortality using case–control and cohort studies. Methods: We searched Medline, Embase and Web of Knowledge for relevant articles published up to January 2015. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Results: A total of 10 case–control and six cohort studies involving 8145 patients were analyzed. The overall analysis indicated that PPI use was associated with SBP (OR = 2.11, 95% CI: 1.46–3.06). The association was limited in case–control studies (OR = 2.97, 95% CI: 2.06–4.26) but not in cohort studies (OR = 1.18, 95% CI: 0.99–1.14). PPI therapy was not associated with mortality during hospitalization or within 30 days after SBP (OR = 1.54, 95% CI: 0.92–2.59). Conclusions: We could not establish causality that PPI use increases the incidence or mortality of SBP.